1998
DOI: 10.1063/1.122194
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of hydrogenated amorphous silicon p–i–n solar cells with two-step i layers guided by real-time spectroscopic ellipsometry

Abstract: Hydrogenated amorphous silicon (a-Si:H) p–i–n solar cell performance has been optimized using a two-step i-layer growth process. This effort has been guided by real-time spectroscopic ellipsometry (RTSE) studies of the nucleation and growth of a-Si:H films by plasma-enhanced chemical vapor deposition at 200 °C using a variable H2-dilution gas flow ratio R=[H2]/[SiH4]. RTSE studies during film growth with R>15 reveal a transition from the amorphous to microcrystalline (a→μc) phase at a critical thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(163 citation statements)
references
References 11 publications
8
155
0
Order By: Relevance
“…13 Thus, care has to be taken when transferring our observations to layers grown on other substrates. In particular, our observations of the variety of microstructures grown on glass substrates call now for the study of the microstructure of intrinsic c-Si:H layers grown within p-i-n devices.…”
Section: Resultsmentioning
confidence: 99%
“…13 Thus, care has to be taken when transferring our observations to layers grown on other substrates. In particular, our observations of the variety of microstructures grown on glass substrates call now for the study of the microstructure of intrinsic c-Si:H layers grown within p-i-n devices.…”
Section: Resultsmentioning
confidence: 99%
“…The buffer layer is highly diluted with H 2 which promotes a better quality and a higher band gap material. 18,21,22 In Sec. III D, we demonstrated that the buffer layer improves slightly the V oc and reduces mainly the series resistance of the a-Si: H solar cell and thus improves the FF of the a-Si: H solar cell.…”
Section: Discussionmentioning
confidence: 99%
“…It increases the band gap of a-Si: H, which should act as a graded interface between the i-layer and the n-SiC layer, and reduces the density of defects at the n / i interface. 18,21,22 Figure 10 shows the efficiencies of the cell with and without buffer layer for different surface treatment times on the ZnO LP-CVD. Table II the buffer layer is mostly in FF ͑63.4% ⇒ 67.6%͒ and slightly in V oc ͑885 mV⇒ 895 mV͒.…”
Section: Buffer Layer At N / I Interfacementioning
confidence: 99%
“…The life-motif of improving stability against photodegradation of a-Si:H led researchers to demonstrate recently that "protocrystalline Si", produced near the amorphous-to-microcrystalline silicon transition regime, exhibits a higher degree of ordering with increased stability under light illumination [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][22][23][24][25][26] or without H 2 dilution [27][28][29][30][31][32][33][34], in the course of years various halogenated Si gas precursors, e.g. SiF 4 [35][36][37][38][39][40], SiCl 4 [41][42][43], and SiH 2 Cl 2 [44,45] have also been investigated and reported.…”
Section: Introductionmentioning
confidence: 99%